The quest for axions and other new light particles. Issue 6 (11th June 2013) - Baker, K.; Cantatore, G.; Cetin, S. A.; Davenport, M.; Desch, K.; Döbrich, B.; Gies, H.; Irastorza, I. G.; Jaeckel, J.; Lindner, A.; Papaevangelou, T.; Pivovaroff, M.; et al.
<x xml:space="preserve">Abstract</x> Standard Model extensions often predict low‐mass and very weakly interacting particles, such as the axion. A number of small‐scale experiments at the intensity/precision frontier are actively searching for these elusive particles, complementing searches for physics beyond the Standard Model at colliders. Whilst a next generation of experiments will give access to a huge unexplored parameter space, a discovery would have a tremendous impact on our understanding of fundamental physics.